KONSTRUKSI SOSIAL SHOPPER TERHADAP KEPUTUSAN PEMBELIAN DENGAN AKUN TIKTOK NATASHA SURYA SEBAGAI REFRENSI (The Commercium, 2023)
Currently, social media TikTok is one of the most popular applications today, which makes social media much loved by the public. Social media TikTok is then widely used by business actors to introduce and protect its existence. One of the individuals or content creators who implement marketing strategies using their own social media is Natasha Surya. This study aims to find out how the social construction of shoppers as consumers who make purchases online after seeing a review of the TikTok content @natasha.surya. This study uses the theory of Social Construction from Peter L. Berger and Thomas Luckman which takes place in three stages, namely externalization, objectivation, and internalization. This study uses a qualitative research method with a phenomenological approach. Collecting data through observation, interviews, and documentation. The results of this study are the influence of informative explanations that give rise to variety seeking behavior in shoppers. There is ease in finding the desired product because of the detailed information and visual content displayed. Until finally causing impulsive behavior in the shopper.